Evaluation of Accounting Information Systems on Cash Receiving and Distribution Procedures at Semen Padang Large Family Cooperatives (KKSP) at Unit Services - Rinanda, Yessi (Dinasti Publisher, 2021)
The purpose of this study is to explain how the accounting information system for cash receipts and cash disbursements procedures and the problems that exist in the department store unit at the large family cooperative of PT Semen Padang. This research uses a descriptive method. The results of the study explain that: 1) Documents used are complete, 2) Functions related to cash receipts and disbursements have been running well, because they have separated functions, 3) Cash receipts and disbursements procedures at department stores implemented by KKSP have been running. well and is the same as theory, 4) Internal control of cash receipts and disbursements has been implemented properly and sound practices are found in cash management.